Pengaruh Motivasi Instrinsik dan Motivasi Ekstrinsik Terhadap Proses Pembelajaran Mahasiswa Universitas Pendidikan Indonesia - ., Rena Rismayanti; ., Muhammad Aththar Rayhan; ., Qois Khairullah El Adzim; ., Lu’lu Alikadhiya Fatihah (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
The purposes of the research we conducted were (1) to analyze how much influence the result of intrinsic motivation has on the learning process of indonesian university of education students (2) to analyze how much influence the result of extrinsic motivation has on the learning process of indonesian university of education students and (3 ) to analyze how much influence is generated from both, namely from intrinsic motivation and extrinsic motivation on the learning process of indonesian university of education students. This research was conducted using qualitative methods with collection techniques through interviews, distributing questionnaires and questionnaires. The data analysis technique used is the research instrument test including: validation test and reliability test, based on the research we have done we get the results that (1) intrinsic motivation greatly influences the learning process of indonesian university of education students because when someone has an interest in learning within themselves then he will have the drive to achieve the expected goals. (2) extrinsic motivation also greatly influences the learning process of indonesian university of education students because when someone occupies a comfortable learning environment, a stronger enthusiasm for learning will arise as well. And (3) it can be concluded that intrinsic motivation and extrinsic motivation greatly influence the learning process of indonesian university of education students and the two also have a very close relationship because when a person only has intrinsic motivation and is not balanced with a good learning environment, the learning outcomes obtained will decrease.